KAJIAN HISTORIS MAQASHID SYARIAH SEBAGAI TEORI HUKUM ISLAM - Ahmad Farikhin; Ahmad Hasan Ridwan; Heni Mulyasari (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2022)
The term maqashid was first proposed by al-Hakim al-Tirmidzy in the third century Hijiriyah, but has been conceptually invented and used since prophetic times with different terms. This study aims to find historical traces of maqashid sharia from original sources from time to time as sources of Islamic law after the Quran, Hadith, Ijma and Qiyas, which are discussed by contemporary scholars as solutions and breakthroughs in answering the legal vacuum caused by rapid changes. This research uses the istiqrai tahlili bayani method which focuses on tracing the traces of maqashid in Islamic scientific treasures. This research concludes that: First, maqashid sharia as a theory of Islamic law as it is known today by al-Juwaeny and elaborated by his disciple named al-Ghazaly later became a comprehensive scientific discipline by al-Syathiby in the eighth century Hijri; Secondly, the discussion of maqashid in this century has developed further with the addition of al-dharuriyat points according to the essential needs of contemporary Muslims such as guarding the people and the state not only sufficiently guarding al-dharuriyat but needing the development of al-dharuruyat points in order to support the progress of Muslims in various spheres of life; Third, maqashid sharia is the result of ijtihad that can change and develop according to the demands of progress as a solution that Islam can offer to the challenges of the times as initiated by Auda.